2023
DOI: 10.1101/2023.10.24.563880
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Hao-Fountain syndrome protein USP7 regulates neuronal connectivity in the brain via a novel p53-independent ubiquitin signaling pathway

Hao Chen,
Cole J. Ferguson,
Dylan C. Mitchell
et al.

Abstract: The development of the brain relies on precise control of protein ubiquitination and degradation, and hence, deregulation of ubiquitination signaling networks is thought to play an important role in neurological disorders. Mutation or deletion of the deubiquitinase USP7 causes the Hao-Fountain syndrome, characterized by developmental delay, intellectual disability, autism, and aggressive behavior. Although USP7 function has been studied in proliferating cells in the context of cancer biology, the roles and mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Studies in mice indicated that loss of USP7 also affects (neuro)development via p53-directed control of cell proliferation and survival. 14,15,54 Another function of USP7 that has been linked to Hao-Fountain syndrome is the regulation of endosomal recycling through stabilization of a MAGEL2-TRIM27 complex. 1 However, our results do not support a role for TRIM27 in neuronal differentiation (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in mice indicated that loss of USP7 also affects (neuro)development via p53-directed control of cell proliferation and survival. 14,15,54 Another function of USP7 that has been linked to Hao-Fountain syndrome is the regulation of endosomal recycling through stabilization of a MAGEL2-TRIM27 complex. 1 However, our results do not support a role for TRIM27 in neuronal differentiation (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, USP7 was implicated in regulation of neuronal connectivity in the mouse brain via splicing factor PPIL4. 54 Suggestively, in addition to BCOR-ncPRC1.1, USP7 has other targets that have been associated…”
Section: Discussionmentioning
confidence: 99%